2013
DOI: 10.5897/ajb2013.12027
|View full text |Cite
|
Sign up to set email alerts
|

Protein landmarks for diversity assessment in wheat genotypes

Abstract: Grain proteins from 20 Indian wheat genotypes were evaluated for diversity assessment based seed storage protein profiling on sodium dodecylsulphate polyacrylamide gel electrophoresis (SDS-PAGE). Genetic diversity was evaluated using Nei's index, Shannon index and Unweighted pair group method with arithmetic mean (UPGMA) cluster analysis by constructing dendrogram of fractions of proteins, which were used for the calculation of similarity coefficients between these varieties. Diversity analysis attributes exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Production of wheat is focused primarily in China, Russia, Turkey, Indian, Ukraine, Australia, United States, and Pakistan, accounting for above 80% of the global wheat production (Ikhtiar and Alam, 2007; Siddiqui and Naz, 2009; Sun et al, 2014). Pakistan is the eighth leading producer of wheat, accounting for almost 3.17% of the wheat output in the world from 3.72% of the area under wheat cultivation (Shuaib et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Production of wheat is focused primarily in China, Russia, Turkey, Indian, Ukraine, Australia, United States, and Pakistan, accounting for above 80% of the global wheat production (Ikhtiar and Alam, 2007; Siddiqui and Naz, 2009; Sun et al, 2014). Pakistan is the eighth leading producer of wheat, accounting for almost 3.17% of the wheat output in the world from 3.72% of the area under wheat cultivation (Shuaib et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other authors have demonstrated the usefulness of PCR-based analysis for distinguishing between cultivars with different HMW glutenin subunits [27][28][29][30]. Allelic variations in Glu-A1, Glu-B1, and Glu-D1 were reported to have strong association with gluten strength [8,[31][32][33]. Low molecular weight glutenin subunits are about one-third of the total seed protein and 60% of total glutenin [34].…”
Section: Wheatmentioning
confidence: 99%
“…The fatty acids are primarily linoleic acid (18:2), palmitic acid (16:0), and oleic acid (18:1) [5] . The wheat germ was also reported as one of the most highly concentrated parts of mineral salts such as magnesium, calcium, manganese, zinc, and potassium, in descending order [6,7]. In addition, wheat germ also contains bioactive compounds such as riboflavin (6-10 mg/kg), phytosterols (24-50 mg/kg), carotenoids (4-38 mg/kg), policosanols (10 mg/kg), thiamin (15-23 mg/kg) and tocopherols (300-740) mg/kg.…”
Section: Introductionmentioning
confidence: 99%